ANALISIS FAKTOR YANG MEMPENGARUHI KEGAGALAN TIM SEPAK BOLA PERSANUBARI LOLOS TURNAMEN LIGA 1 ASKAB FLORES TIMUR - antonius28rn (Indonesia Sport Journal, 2025)
This study aims to analyze the factors contributing to the failure of Persanubari Riangkotek Team in promoting to the East Flores District Football Association (ASKAB) League 1. The research employs a qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. Data were analyzed using Miles and Huberman's interactive analysis model, including data reduction, data display, and conclusion drawing. The findings indicate that the team's failure stems from internal and external factors. Internal factors include unprofessional management, inconsistent training programs, inadequate facilities, recruitment based on personal connections, and internal conflicts. External factors encompass poor field conditions, inconsistent supporter support, community interference, and lack of media exposure. Source triangulation was used to validate the research findings. The analysis reveals that an unclear organizational structure and overlapping roles further hinder the team's performance. To achieve promotion to League 1, comprehensive improvements are needed in financial management, sustainable player development, facility upgrades, and organizational restructuring.